One-Year Prevalence Rates of Major Depressive Disorder in First-Year University Students - Price, E. Lisa; McLeod, Peter J.; Gleich, Stephen S.; Hand, Denise (Canadian Journal of Counselling and Psychotherapy, 2007)
First-year university students may be more at risk for experiencing Major Depressive Disorder (MDD) than the general population given associated risk factors of this age range. A two-phase procedure was used to estimate the one-year prevalence rate of MDD and comorbid Major Anxiety Disorders among first-year university students at a small Canadian university. The results of the study indicate that approximately 7% of men and 14% of women in their first year met the criteria for MDD. Further, about 13% of men and 19% of women met the criteria for a Major Anxiety Disorder. Implications of these findings are discussed.